Before reaching the finish line: incompletion of the tenth grade of schooling in Nepal - Thapa, Shyam; Paul, Pintu (Frontiers in Education, 2024)
ObjectiveIncompletion of the basic levels of education is known to adversely affect the social and economic well-being of individuals, as well as a nation’s prosperity. This paper analyzes the correlates of selected characteristics associated with the incompletion of 10th grade among students in Nepal.Data and methodsData on 2,812 youth in ages 18–24, extracted from the 2016 Nepal Demographic and Health Survey, are used to analyze the proportion of youth who did not complete the 10th grade. The variations by contextual, household, and individual characteristics are analyzed through descriptive and multivariate logistic regression.ResultsAmong the age group of 18–24, the majority – 64% of males and 69% of females – did not complete secondary school. Household wealth showed a consistent and strong effect on incompletion. Overall, the household wealth variable accounted for much of the variation in the incompletion of the 10th grade across the country’s provinces. Additionally, being married is associated with a higher likelihood of incompletion of secondary school, net of the influence of other factors.ConclusionIn Nepal, a significant number of students do not complete the 10th grade of schooling. Sustained efforts, through targeted policies and interventions, are needed to ensure that students who begin secondary school do not leave before completing their education.